Reflection of the national vision of the world in phraseological units - Abdi, Mamatov; Umarova, Sayyorakhon; Aliqulova, Dildora; Hamida, Jurakobilova; Bekmuradova, Zebiniso (Linguistics and Culture Review, 2021)
This research paper is devoted to the thorough study of phraseological units in terms of national connotation. Phraseological units that reflect national and cultural identity are the beauty and art of language. Phraseologisms, by their very nature, are a means of expressing imagery in a language, but they also serve to reveal the national culture, character, humor, grief, and anxiety of a people. For this reason, phraseology is the most important unit of poetic language used in the literary text to fully express the image, character, character, and to illustrate and exaggerate events, happenings, and situations. The phraseological resources of each language reflect the socio-historical events, moral and spiritual-cultural norms, mental and psychological conditions, religious ideas, national traditions, and customs of the people. Such phraseologies belonging to the vocabulary of a particular language community are among the national language tools. They polish the national color of the work of art and create a strong emotionality while emphasizing the popularity and originality of the language.